Immature buffalo (Bubalus bubalis) oocytes vitrification: Effect of ethylene glycol concentrations on survivability and nuclear maturation - BOMBATKAR, R S; PAWSHE, C H; CHAUHAN, M S; RAUT, P B (The Indian Journal of Animal Sciences, 2010)
The objective of the present research work was to study the effect of 5, 6 and 7 M ethylene glycol (EG) concentrations during vitrification of immature buffalo oocytes. The COCs were retrieved by aspirating visible follicles on the ovaries collected from slaughterhouse and loaded into 0.25 ml French straws after exposing to the equilibration medium (50% VS v/v in DPBS) for 1 min and the final vitrification solutions of respective concentrations of EG. The straws were then directly plunged into the LN2. After thawing in warm water (28–30°C), for equilibration COCs were kept for 4 step dilutions step-wise in 0.5, 0.33, 0.17 and 0.00 M sucrose holding medium for 5 min each. The percent morphologically normal oocytes recovered were significantly higher (75.00%) in 7 M concentration. For nuclear maturation, the COCs were placed in 50 μl droplets of maturation medium and cultured for 24 h in CO2 incubator at 39°C temperature. The proportion of maturation reached to metaphase-II was significantly higher in 7 M (47.42%) concentration whereas the highest nuclear degeneration was in 6 M (70.47%) concentration. From the results, it was revealed that 7 M concentration has beneficial effect on survivability and nuclear maturation of oocytes.